Natural manganese ores for efficient removal of organic pollutants via catalytic peroxymonosulfate-based advanced oxidation processes - Yao, Z.; Chen, R.; Han, N.; Sun, H.; Wong, N.H.; Ernawati, L.; Wang, Shaobin; Sunarso, J.; Liu, Shaomin (2023)
Peroxymonosulfate-based advanced oxidation processes (PMS-AOPs) for in situ persistent organic pollutant (POP) remediation in aqueous solutions can be a promising technology. However, this technology is constrained by its high toxicity and cost of metal oxide and non-metal catalysts for PMS activation. Here, we investigated the catalytic performance of a widely available natural mineral, manganese ore (MO), for PMS activation. A series of natural MO samples in an aqueous solution were prepared via the Fenton-like reaction. The samples' crystalline structure, surface morphology, textural properties, and other surface characteristics of the selected MO were systematically characterized. The effects of PMS concentration and process parameters on the degradation performance of four chosen model pollutants, that is, phenol, tetrabromobisphenol A (TBBPA), rhodamine B (RhB), and methylene blue (MB), were evaluated. The experimental results showed that natural MO increased catalytic activity and enhanced the PMS oxidation processes, with 98%, 90%, and 75% removal efficiencies on phenol, TBBPA, and RhB, respectively, within 1.5 h. The reduction in the initial pH solution from 10 to 7 and the increase in temperature from 15 to 45°C enhanced the MB degradation rate (decolorization) by 55 and 46%, respectively, within 2 h. During the PMS activation process, SO4•−, •OH, and 1O2 species were generated, but only SO4•− and •OH radicals with strong oxidative potentials contributed to the catalytic degradation. The dissolved metals from the experiments were found well within the limit of drinking water standards, verifying that the MO + PMS catalytic system is suitable for commercial applications. This work provides insights into the development potential and prospects of using natural minerals for PMS activation and POP degradation, which can accelerate their industrial applications.